Expression analysis in self-compatible Petunia hybrida and promoter analysis of S-locus F-box genes/SLFs in Petunia inflata - Liu, Chen (2021)
Self-incompatibility (SI), a type of intraspecific reproductive barrier occurs widely in flowering plants and helps to avoid inbreeding and protects the genetic diversity of a population. When the pollen lands on a self-pistil, SI will prevent fertilization; when the pollen lands on the pistil of an unrelated plant, fertilization will not be affected. SI consists of two types: Sporophytic SI (SSI) and gametophytic SI (GSI). In GSI it is the haploid genotype of the pollen itself that controls the pollen phenotype. Transgenic studies in Petunia have shown that the pistil phenotype is determined by a stylar ribonuclease (S-RNase). In the fertilization process, Slinked F-box genes/SLFs that are expressed in pollen work together with S-RNases to determine the outcome of a pollination. Recently up to 20 SLF genes have been reported at the S-locus in Petunia, but the exact role of individual SLFs in controlling the phenotype is still not clear. Part of this project aims to investigate SLF expression between two closely linked varieties of Petunia hybrida, which have different phenotypes. A combination of RT-PCR and qRT-PCR using specific primers were used to determine the expression patterns of individual SLF genes in these two varieties. The results of RT-PCR and qRT-PCR indicate that all SLFs express in these two varieties, and most SLFs share significant differences in the expression levels comparison between these two closely linked varieties of Petunia hybrida. The partial DNA sequences of SLFs in these two varieties are proved that is identical. Therefore, the different expression level of SLFs might is the cause of the different SI between these two closely linked varieties of Petunia hybrida. The finding of this part of this project might be able to provide some evidence in the evolution theory of SI plants.